Simulating reading acquisition: The link between reading outcome and multimodal brain signatures of letter–speech sound learning in prereaders - Iliana I. Karipidis (Nature Portfolio, 2018)
Abstract During reading acquisition, neural reorganization of the human brain facilitates the integration of letters and speech sounds, which enables successful reading. Neuroimaging and behavioural studies have established that impaired audiovisual integration of letters and speech sounds is a core deficit in individuals with developmental dyslexia. This longitudinal study aimed to identify neural and behavioural markers of audiovisual integration that are related to future reading fluency. We simulated the first step of reading acquisition by performing artificial-letter training with prereading children at risk for dyslexia. Multiple logistic regressions revealed that our training provides new precursors of reading fluency at the beginning of reading acquisition. In addition, an event-related potential around 400 ms and functional magnetic resonance imaging activation patterns in the left planum temporale to audiovisual correspondences improved cross-validated prediction of future poor readers. Finally, an exploratory analysis combining simultaneously acquired electroencephalography and hemodynamic data suggested that modulation of temporoparietal brain regions depended on future reading skills. The multimodal approach demonstrates neural adaptations to audiovisual integration in the developing brain that are related to reading outcome. Despite potential limitations arising from the restricted sample size, our results may have promising implications both for identifying poor-reading children and for monitoring early interventions.